Предмет: Математика,
автор: Анюта0966
3(3x-1)+5=8(x+2)+3
-4,5(x+3)-1=7,2-5(x-2)
Ответы
Автор ответа:
0
3(3x-1)+5=8(x+2)+3
9х-3+5=8х+16+3
9х-8х=16+3+3-5
х=17
-4,5(x+3)-1=7,2-5(x-2)
-4,5х-13,5-1=7,2-5х+10
-4,5х+5х=13,5+1+7,2+10
0,5х=31,7
х=31,7 / 0,5
х=63,4
9х-3+5=8х+16+3
9х-8х=16+3+3-5
х=17
-4,5(x+3)-1=7,2-5(x-2)
-4,5х-13,5-1=7,2-5х+10
-4,5х+5х=13,5+1+7,2+10
0,5х=31,7
х=31,7 / 0,5
х=63,4
Автор ответа:
0
3(3x-1)+5=8(x+2)+3
9х-3+5=8х+16+3
9х-8х=16+3+3-5
х=17
ОТВЕТ: х=17
-4,5(x+3)-1=7,2-5(x-2)
-4.5х-13.5-1=7.2-5х+10
-4.5х+5х=7.2+10+13.5+1
0.5х=31.7
х=31.7:0.5
х=63.4
ОТВЕТ: х=63.4
9х-3+5=8х+16+3
9х-8х=16+3+3-5
х=17
ОТВЕТ: х=17
-4,5(x+3)-1=7,2-5(x-2)
-4.5х-13.5-1=7.2-5х+10
-4.5х+5х=7.2+10+13.5+1
0.5х=31.7
х=31.7:0.5
х=63.4
ОТВЕТ: х=63.4
Похожие вопросы
Предмет: Қазақ тiлi,
автор: MaliaBlackTea
Предмет: Физика,
автор: madinabekbolat2007
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: Информатика,
автор: DaffyDuck